Influence of health literacy and self-management on quality of life among older adults with hypertension and diabetes in Northwest China - Yiliyaer Aihemaiti; Zhihong Li; Ying Tong; Lijun Ma; Fang Li (Experimental Gerontology)
Objective: This study investigated the relationship between health literacy, self-management, and quality of life among older adults diagnosed with hypertension and diabetes. Additionally, the influence of these factors on quality of life was assessed to provide a theoretical basis for enhancing the well-being of individuals with chronic conditions. Methods: A cohort of 600 older adults diagnosed with hypertension and diabetes were recruited in Xinjiang, China. Data were collected through a questionnaire survey, and the relationship between health literacy, self-management levels, and quality of life were analysed using a structural equation model (SEM). Results: Of the 600 distributed questionnaires, 556 were completed. Among the older adults with hypertension and diabetes, 17 (3.0 %) demonstrated very adequate health literacy, 188 (33.8 %) had adequate health literacy, 67 (12.1 %) exhibited possible insufficient health literacy, and 284 (51.1 %) were categorized as having insufficient health literacy. The mean self-efficacy score was 6.97 ± 1.03, reflecting low levels of self-management. The average Physical Component Summary score for quality of life was 51.10 ± 12.80, while the average Mental Component Summary score was 70.89 ± 9.43. SEM analysis indicated that quality of life exerted a significant positive effect on health literacy (β = 0.369, P < 0.001) and self-management (β = 0.133, P < 0.01). Furthermore, health literacy was found to significantly positively influence self-management (β = 0.210, P < 0.01). Conclusion: Quality of life in older adults with chronic conditions is significantly influenced by their health literacy and self-management levels. Higher health literacy and improved self-management are associated with enhanced overall quality of life.